Glycaemic and insulinaemic responses of adult healthy warm‐blooded mares following feeding with Jerusalem artichoke meal. (19th June 2017) - Glatter, M.; Bochnia, M.; Goetz, F.; Gottschalk, J.; Koeller, G.; Mielenz, N.; Hillegeist, D.; Greef, J. M.; Einspanier, A.; Zeyner, A.
Summary: This study aimed to investigate the impact of the supplementation of a pre‐biotic compound [Jerusalem artichoke meal (JAM)] on the glycaemic and insulinaemic response in healthy, non‐obese warm‐blooded horses. Six adult mares [mean body weight (bwt) 529 ± 38.7 kg; body condition score 5.1 ± 0.49/9] were used. In two equal meals per day, the horses received crushed oat grains (1 g starch/kg bwt per day) and meadow hay (2 kg/100 kg bwt per day) which together were likely to meet the energy recommendation for light work (GfE, 2014 ). Additionally, they received either 0.15 g fructo‐oligosaccharides and inulin (FOS+INU)/kg bwt per day via commercial JAM or maize cob meal without grains as control (CON) in 2 × 3‐week periods according to a crossover design. Blood was collected on d21 of the feeding period at different ante‐ and postprandial (PP) time points (−60, 0, 30, 60, 90, 120, 180, 240 and 300 min), and the plasma glucose and serum insulin levels were determined. Feeding JAM vs. CON did not change the PP peak of glucose or insulin (glucose: 6.3 ± 0.40 vs. 7.0 ± 0.87 mmol/l; insulin: 0.508 ± 0.087 vs. 0.476 ± 0.082 nmol/l) nor did it cause different AUCs until 120 and 300 min PP for glucose and insulin, respectively (AUC120, glucose: 997 ± 41.6 vs. 1015 ± 41.63 mmol/l per minute, insulin: 49 ± 6.3 vs. 42 ± 6.3 nmol/l per minute; AUC300, glucose: 1943 ± 142.3 vs. 2115 ± 142.3 mmol/l per minute, insulin: 94 ± 14.8 vs. 106 ± 14.8 nmol/l per minute; p > 0.05). Following JAM vs. CON feeding, glucose and insulin levels declined more rapidly until 240 min PP and tended to be lower (p = 0.053 and p = 0.056, respectively) at this time point. This result might be promising and should further be studied more detailed.